2015
DOI: 10.1089/apc.2015.0038
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Reducing Other HIV Risk-Reduction Practices if Taking Pre-Exposure Prophylaxis: Findings from a Qualitative Study Among Women in Kenya and South Africa

Abstract: Findings from a survey conducted among women at high risk for HIV in Bondo, Kenya, and Pretoria, South Africa, demonstrated that a substantial proportion would be inclined to reduce their use of other HIV riskreduction practices if they were taking pre-exposure prophylaxis (PrEP). To explore the motivations for their anticipated behavior change, we conducted qualitative interviews with 60 women whose survey responses suggested they would be more likely to reduce condom use or have sex with a new partner if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Very few studies reported clear opposition to PrEP as an HIV prevention tool, although some generated evidence of community distrust of study/trial designs or of the concept of PrEP itself [21]. Theoretical studies among potential end-users typically found high acceptability of PrEP [22][23][24][25][26][27][28][29][30][31]. By including the theoretical research, a range of regimens are included in the review including: oral daily and intermittent (the definition of which is particular to the given study), as well as emerging injectable and vaginal ring products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few studies reported clear opposition to PrEP as an HIV prevention tool, although some generated evidence of community distrust of study/trial designs or of the concept of PrEP itself [21]. Theoretical studies among potential end-users typically found high acceptability of PrEP [22][23][24][25][26][27][28][29][30][31]. By including the theoretical research, a range of regimens are included in the review including: oral daily and intermittent (the definition of which is particular to the given study), as well as emerging injectable and vaginal ring products.…”
Section: Resultsmentioning
confidence: 99%
“…Even within marriage and during pregnancy, women worried partners might “bring HIV into the home” . Many women only acknowledged risk of HIV infection within their primary relationship but fear of rape and other violence was also cited as a motivator for PrEP use .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary purpose of the follow-up interviews was to explore women's motivations for reducing the use of other HIV risk-reduction practices if they were to take PrEP (Corneli, Namey, et al 2015). We also wanted to understand the context of these women's sexual lives and decision-making as it related to starting and stopping PrEP, so that their experiences and motivations might inform counselling around PrEP discontinuation.…”
Section: Methodsmentioning
confidence: 99%
“…Many also believed that PrEP alone would be a sufficient HIV risk-reduction strategy. 5 These results highlighted the necessity of having guidance that encourages informed decision-making by providing essential HIV prevention information within the context of PrEP while helping women to reflect upon the information within their own values and risk situations and apply the information to their individual needs and circumstances.…”
mentioning
confidence: 97%